2016
DOI: 10.1590/s1677-5538.ibju.2015.0743
|View full text |Cite
|
Sign up to set email alerts
|

A large 15 - year database analysis on the influence of age, gender, race, obesity and income on hospitalization rates due to stone disease

Abstract: Purpose:To assess the public hospitalization rate due to stone disease in a large developing nation for a 15-year period and its association with socio-demographic data.Materials and Methods:A retrospective database analysis of hospitalization rates in the Brazilian public health system was performed, searching for records with a diagnosis code of renal/ureteral calculi at admission between 1998–2012. Patients managed in an outpatient basis or private care were excluded. Socio-demographic data was attained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
59

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(64 citation statements)
references
References 15 publications
(20 reference statements)
2
3
0
59
Order By: Relevance
“…[3] The mean age in our study of 48.2 years ± 12.4 (SD) was similar to that reported by Aghamir et al [6] with majority of their patients in the middle-age group. There is a slight female preponderance in our study; this is similar to the finding by Mello et al [7] but at variance with most of the other previous studies which reported male preponderance. [38] Estrogen has been shown to be protective for stone;[9] the female preponderance in our study can be explained by the fact that majority of the patient were middle-age group during which many of the female were peri/postmenopausal.…”
Section: Discussionsupporting
confidence: 92%
“…[3] The mean age in our study of 48.2 years ± 12.4 (SD) was similar to that reported by Aghamir et al [6] with majority of their patients in the middle-age group. There is a slight female preponderance in our study; this is similar to the finding by Mello et al [7] but at variance with most of the other previous studies which reported male preponderance. [38] Estrogen has been shown to be protective for stone;[9] the female preponderance in our study can be explained by the fact that majority of the patient were middle-age group during which many of the female were peri/postmenopausal.…”
Section: Discussionsupporting
confidence: 92%
“…From 2017 to 2019, a mean increment of 6.4% hospital admissions was observed, reaching 90.170 events. These data reinforce previous surveys demonstrating a progressive increase in urolithiasis admissions over the years in Brazil (12). Conversely, during the COVID-19 outbreak, there was a significant decrease in hospital admissions with urolithiasis diagnosis compared to preceding years (p <0.0001, Figure -1).…”
Section: Resultssupporting
confidence: 89%
“…Consistent with the literature, our findings support that the incidence of urolithiasis was greater in the younger individuals even though there was no statistical significance. The increased incidence of urolithiasis in middle age may be associated with the development of metabolic syndrome, increased dietary calcium, sucrose or protein intake, and increased working time [ 2 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence means any stone during a period of life and the lifetime prevalence of urolithiasis would increase with incremental age [ 1 ]. The incidence of urolithiasis varies with age and it is rare before age 20; nevertheless, urolithiasis would peak between age 40–60 and then decrease after age 65 [ 2 ]. The annual incidence of urolithiasis is reported to range between 0.5% and 1.5% in Western countries, but the epidemiological studies of incidence in Taiwan is limited [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%